The Function of Persembahan Dance in Malay Weddings in Kampung Besar Seberang Village - Nurjanah, Ila Ana; Nerosti (Universitas Negeri Padang, 2023)
This study aims to describe and analyze the Functions of Persembahan Dance in the Malay Community Wedding Party in Kampung Besar Seberang Village, Rengat District, Indragiri Hulu Regency, Riau Province. The type of research used is qualitative research with analytical descriptive methods. Data collection techniques used are literature study, observation, interviews and documentation. The types of data used are primary data and secondary data. The data analysis technique used is by selecting data, analyzing data, and interpreting and describing the data so as to produce conclusions from what is being studied. The results of the study found that the Persembahan Dance in the Malay community wedding party had 2 dance functions, namely the function of the ceremony and the function of performance or aesthetic presentation. The function of the ceremony, the Persembahan Dance is performed in traditional Malay wedding parties, where this dance is to welcome respected guests, namely a pair of bride and groom sitting side by side in the aisle. The dance ends with the presentation of a betel leaf. Persembahan Dance in traditional Malay weddings today has become a new tradition. Without the Persembahan Dance, the wedding party is not lively. The Persembahan Dance is danced by 5 female dancers with a beautiful, glamorous and majestic impression who prioritizes aesthetics. The Persembahan Dance is deliberately prepared with a varied choreography intended to be shown to the general public to function as a dance performance or an aesthetic presentation.